MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA PIAS-PIAS KATA DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS 1 MI MIFTAHUL ULUM SENTUL SUMBERSUKO LUMAJANG TAHUN AJARAN 2022/2023 - Ni’mah Lailatul Mas’adah (Universitas Islam Raden Rahmat Malang, 2023)
Reading is an activity carried out to obtain information, knowledge and new experiences. The reading process consists of several aspects, including the sensory aspect which is the ability to use written symbols, the perceptual aspect which is the ability to interpret what is seen as a symbol, the schemata aspect which is the ability to connect written information with existing knowledge structures, the thinking aspect which is the ability make inferences and evaluations fom the material that has been studied, the affective aspect is the aspect relating to the reader's interest which influences reading activities. The aim of this research is: The aim of this research is to improve the initial reading ability of grade 1 students at MI Miftahul Ulum Sentul for the 2022-2023 academic year by using word-pias media. This research uses a qualitative-descriptive method, with a case study approach. Data collection techniques use in-depth interviews, observation and documentation. The data analysis uses data reduction, data presentation, and drawing conclusions. The results of the research describe that) According to planning, the things that teachers do in planning learning media are by making lesson plans that use word-pias media, as well as making observation sheets to determine the level of studentds reading ability. 2) according to implementation t can be seen that after using pias-pias media said students become more interested in learning to read so that student’s reading abilities improve.